Cysteine-Rich Peptide Fingerprinting as a General Method for Herbal Analysis to Differentiate Radix Astragali and Radix Hedysarum - Huang, Jiayi; Wong, Ka H.; Tay, Stephanie V.; How, Adrian; Tam, James P. (Frontiers in Plant Science, 2019)
Species misidentification and adulteration are major concerns in authenticating herbal medicines. Radix Astragali (RA), the roots of Astragalus membranaceus, is a traditional herbal medicine used for treating diabetes. However, it is often substituted by Radix Hedysarum (RH), the roots of Hedysarum polybotrys from the same plant family Fabaceae, which possesses different bioactivities. Current authentication methods, focusing on the chemical composition differences of herbal medicines based on small molecules, have limitations when these chemical markers are found in many species. Herein, we describe a rapid and general method using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), coupled with multivariate analyses to differentiate herbal medicines. We used cysteine-rich peptide (CRP) fingerprinting, a method that exploits an underexplored chemical space between 2 to 6 kDa and which is populated by highly stable CRPs. To show the generality of the method, we screened 100 medicinal plant extracts and showed that CRP fingerprints are unique chemical markers. In addition, CRP fingerprinting was many-fold faster than the conventional authentication method using ultra-performance liquid chromatography (UPLC). Multivariate analyses showed that it has comparable classification accuracy as UPLC fingerprinting. Together, our findings revealed that CRP fingerprinting coupled with multivariate analyses is a rapid and general method for authentication and quality control for natural products in medicinal plants.